Leadership competencies for medical education and healthcare professions: population-based study. Issue 2 (27th March 2012) - Çitaku, Fadil; Violato, Claudio; Beran, Tanya; Donnon, Tyrone; Hecker, Kent; Cawthorpe, David
Abstract : Objective: To identify and empirically investigate the dimensions of leadership in medical education and healthcare professions. Design: A population-based design with a focus group and a survey were used to identify the perceived competencies for effective leadership in medical education. Setting: The focus group, consisting of five experts from three countries (Austria n=1; Germany n=2; Switzerland n=2), was conducted (all masters of medical education), and the survey was sent to health professionals from medical schools and teaching hospitals in six countries (Austria, Canada, Germany, Switzerland, the UK and the USA). Participants: The participants were educators, physicians, nurses and other health professionals who held academic positions in medical education. A total of 229 completed the survey: 135 (59.0%) women (mean age=50.3 years) and 94 (41.0%) men (mean age=51.0 years). Measures: A 63-item survey measuring leadership competencies was developed and administered via electronic mail to participants. Results: Exploratory principal component analyses yielded five factors accounting for 51.2% of the variance: (1) social responsibility, (2) innovation, (3) self-management, (4) task management and (5) justice orientation. There were significant differences between physicians and other health professionals on some factors (Wilk's λ=0.93, p<0.01). Social responsibility was rated higher by other health professionals (M=71.09) than by physicians (M=67.12), as was innovation (health professionals M=80.83; physicians M=76.20) and justice orientation (health professionals M=21.27; physicians M=20.46). Conclusions: The results of the principal component analyses support the theoretical meaningfulness of these factors, their coherence, internal consistency and parsimony in explaining the variance of the data. Although there are some between-group differences, the competencies appear to be stable and coherent.